Green synthesis of silver nanomaterials using Ganoderma Lucidum extract as reducing agent and stabilizer with ultrasonic assistance and application as an antibacterial agent - Nguyen, Thu Huong; Nguyen, Vinh Phu; Le, Thi Hoa; Tran, Thai Hoa (Hue University Journal of Science: Natural Science, 2023)
Synthesis of silver nanoparticles (AgNPs) using plant extracts extracted from Ganoderma lucidum in the buffer zone of Bach Ma National Park, Vietnam is a simple, convenient, economical, and environmentally friendly method. This study describes the biosynthesis of silver nanoparticles in both cases with and without ultrasonic assistance using Ganoderma lucidum extract as a reducing and protective agent. Transmission electron microscopy, scanning electron microscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy were used to characterize the as-synthesized AgNPs. Compared to the heating reflux method, the proposed ultrasonic wave assisted heating reflux method produced AgNPs had higher efficiency, smaller and more uniform particle size 6.08 ± 1.80 nm of nm in a short synthesis time period. The antibacterial and antifungal properties of ultrasonically synthesized silver nanomaterials (US-AgNPs) were also investigated. US-AgNPs are important nanomaterials that can find many good applications in practice.